Improving Efficiency of Solar Thermal Flat Plate Collector - Yuthaya Surian, Shesaruben (IRC, 2019)
This project discusses the effect of parameters of Solar Thermal Flat Plate Collector on its overall efficiency.Solar Thermal Flat Plate Collector is the main component of this Solar thermal system.Solar Thermal Flat plate collector is a device which absorbs the incoming solar radiation,converts it into heat, and transfers this heat to a fluid ( usually air,water, or oil) flowing through the collector.This hot water produced will be used for industries such as food, machinery, textile, and pulp and paper industries. However solar thermal system is least utilized in small and medium industries due to poor efficiency which mainly caused by higher heat loss coefficient.The main aim of this study is to understand the working principles of solar thermal flat plate collector and to develop a mathemathical modelling and establish design optimization for Flat Plate Collector using MATLAB.In this project Flat plate collector was chosen because it is cheap,require little maintenance and sufficient for small and medium industry needs.The efficiency improvement methods conducted by other researches have been analysed.